Pickering, M. J., & Garrod, S. (2021). Understanding dialogue: Language use and social interaction. Cambridge University Press. - Li, Yueyuan (Lesya Ukrainka Eastern European National University, 2024)
Understanding Dialogue: Language Use and Social Interaction is written by two prominent psychologists of language. It develops an elegant model to account for the cognitive mechanisms of dialogue. The Shared Workspace Framework for Dialogue is capable of explaining how individuals contribute and control their utterances and how they can manage each other’s contributions and cooperate as one system. I believe this book is worth the attention of all linguists interested in language psychology. First, dialogue is the most fundamental form of language use; second, the theory of dialogue proposed in the book represents a major advancement in the psychology of conversation; third, the theory has a wide range of applications. I believe the current review of the book is the most comprehensive summary and assessment of the book to date.